Management of Acute Appendicitis during the COVID-19 Pandemic - Experience from a Tertiary Level Hospital of Nepal - Pradhan, Susan; Pradhan, Sumita; Kandel, Bishnu Prasad; Lakhey, Paleswan Joshi; Bhandari, Ramesh Singh (Journal of Institute of Medicine Nepal, 2025)
Introduction Appendicitis is the most common abdominal emergency and managed by appendectomy. However, during the peak COVID-19 pandemic most cases of uncomplicated acute appendicitis were managed conservatively and appendectomies were performed only after failure of conservative treatment. The objective of the study was to see the outcome of acute appendicitis treated with conservative management. Methods This was ambispective observational cohort study. All cases admitted as acute appendicitis but managed conservatively during the peak COVID period were collected from record section and patient followed up to five years or till patient got operated. Results A total of 33 cases of uncomplicated appendicitis were admitted, of which 21 cases were managed conservatively.Two cases were lost to follow-up. Of 19 cases, 11 cases (57.89 %) had recurrence and were operated. Among them, ten cases were operated on within 6 months, and 1 case after 8 months of the initial conservative treatment. Among the factors considered for treatment options, Alvarado score 8 (6.5-9) vs 9 (7-9), p=0.03 and Tzanakis score 12 (10-12.5) vs 13 (10-13), p= <0.01 were found to be significant indicators for the conservative and operative management groups. Conclusion Conservative management of uncomplicated appendicitis can be an alternative treatment, particularly during pandemic situations. However, patients with high Alvarado and Tzanakis scores should be closely monitored, with surgical intervention performed if there is recurrence of symptoms.